2012
DOI: 10.1002/jctb.3920
|View full text |Cite
|
Sign up to set email alerts
|

Electro‐membrane reactor for the conversion of lysine monohydrochloride to lysine by in situ ion substitution and separation

Abstract: BACKGROUND: Commercially lysine (Lys) is produced as lysine monohydrochloride (LysCl). The presence of chloride ion (Cl−) in Lys makes it unfit for use in pharmaceutical and livestock feed industries. Various separation methods are required to achieve Lys from fermentation broths. This paper describes an electro‐membrane reactor with three compartments (EMR‐3) for the conversion of LysCl into Lys by in situ ion substitution and separation. RESULTS: The conversion of LysCl into Lys in EMR‐3 is achieved by in si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…IEMs were most widely used in different industries for various separation purposes via the membrane based available techniques such as diffusion dialysis (DD), electrodialysis (ED), Donnan dialysis and electro-membrane reactors. [4][5][6][7][8][9][10] In several industrial production houses like leather, paper, dying and printing, aluminium & tungsten ore smelting as well as man-made ber industries, a great deal of alkaline waste solution is produced which is known to be a major concern from the environmental perspective. 11,12 Thus base recovery from the aqueous waste solution became really crucial for pollution free environment.…”
Section: Introductionmentioning
confidence: 99%
“…IEMs were most widely used in different industries for various separation purposes via the membrane based available techniques such as diffusion dialysis (DD), electrodialysis (ED), Donnan dialysis and electro-membrane reactors. [4][5][6][7][8][9][10] In several industrial production houses like leather, paper, dying and printing, aluminium & tungsten ore smelting as well as man-made ber industries, a great deal of alkaline waste solution is produced which is known to be a major concern from the environmental perspective. 11,12 Thus base recovery from the aqueous waste solution became really crucial for pollution free environment.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al [16] reported the recovery of L-lysine from L-lysine monohydrochloride by ion substitution electrodialysis (ISED, C-A-A configuration), in which the removal ratio of Cl − reached to >95%, but the current efficiency was as low as 20.5%, and the energy consumption was relatively high (9.0 kWh/kg) at the current density of 5-15 mA/cm 2 . Similarly, Kumar et al [17] reported the conversion of lysine monohydrochloride to lysine by ISED (A-A configuration) with the electrolysis reaction, in which the recovery ratio of lysine was 96.2%, the energy consumption was 2.07 kWh/kg, and the current efficiency was 93.2% at the current density of 10 mA/cm 2 . Furthermore, Zhang et al [21] reported the production of L-lysine from L-lysine monohydrochloride by BMED (the BP-A-C configuration, BP-bipolar membrane), in which the removal ratio of Cl − was 86.6%, the current efficiency was 24%, and the energy consumption was as high as 28.2 kWh/kg at the certain conditions.…”
Section: Methodsmentioning
confidence: 93%
“…Cations in the dilute solution migrate through CEM with a direction from the anode to the cathode under the driving force of direct current, while anions in the dilute solution migrate through AEM with the opposite direction [10]. Currently, ED has been used widely in the fields of salt concentration [11], feed desalination [12,13], ion metathesis reaction [14,15], ion substitution [16,17], acid and base production [18][19][20][21][22], etc. For instance, as for the separation of basic amino acid, Kattan Readi et al [23] reported that 1,5 pentanediamine (PDA) can be separated from L-arginine (Arg) by ED at a pH of 10 (PDA +1.5 /Arg ± ) with a high recovery ratio of 63%.…”
Section: Methodsmentioning
confidence: 99%